2021
DOI: 10.1021/acschembio.1c00672
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics-Guided Expansion and Discovery of Graspetides

Abstract: Graspetides are a class of ribosomally synthesized and post-translationally modified peptide natural products featuring ATP-grasp ligase-dependent formation of macrolactones/macrolactams. These modifications arise from serine, threonine, or lysine donor residues linked to aspartate or glutamate acceptor residues. Characterized graspetides include serine protease inhibitors such as the microviridins and plesiocin. Here, we report an update to Rapid ORF Description and Evaluation Online (RODEO) for the automated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…Initially, graspetides were largely identified in various genera of freshwater Cyanobacteria, including the bloom-forming Microcystis and Planktothrix. More recent genome mining efforts have identified graspetides in phyla outside of Cyanobacteria, including numerous terrestrial species. In general, the graspetides are known serine protease inhibitors (Table ).…”
Section: Graspetidesmentioning
confidence: 96%
“…Initially, graspetides were largely identified in various genera of freshwater Cyanobacteria, including the bloom-forming Microcystis and Planktothrix. More recent genome mining efforts have identified graspetides in phyla outside of Cyanobacteria, including numerous terrestrial species. In general, the graspetides are known serine protease inhibitors (Table ).…”
Section: Graspetidesmentioning
confidence: 96%
“…To fill these knowledge gaps, effective tools are urgently needed to monitor the intracellular and extracellular distribution of microviridins and to track the protein targets of microviridin ligands. In addition, 23 further groups of graspetides have recently been discovered or predicted, all of which still await functional characterization [6d] . As an initial step, we planned to develop microviridin chemical probes with functional groups to utilize in biological assays.…”
Section: Introductionmentioning
confidence: 99%
“…Graspetides are defined by the ATP-grasp ligase-dependent formation of macrolactone and macrolactam linkages between the side chains of donor Ser, Thr, or Lys residues and acceptor Asp or Glu residues 2 . Recent bioinformatic studies identified ~4000 graspetide BGCs, split into 24 groups based on sequence similarity of the ATP-grasp enzymes and the presence of conserved motifs within the predicted precursor peptides 14 , 48 , 49 . Eleven graspetide BGCs were refactored in this study and expressed under the four standard conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the graspetides class of RiPPs, only nine of the 24 bioinformatically predicted groups of graspetides have characterized members 14 . Using the FAST-RiPPs pipeline, graspetides were obtained from groups 8 (Gra-7A and Gra-7B), group 19 (Gra-8), and an unnumbered group (Gra-4), expanding the number of characterized groups to 11.…”
Section: Discussionmentioning
confidence: 99%